Promoting Undergraduate Pre-Service Teacher Computational Thinking - Paitoon Pimdee; Sawitree Pipitgool (My University, 2023)
The study aimed to evaluate the results of a computational thinking (CompThink) and learning management model using a flipped classroom (FC), combined with critical thinking problem-solving (CTPS) activities. The sample consisted of 57 third-year Thai computer studies (CS) pre-service teachers (PST) (29 = control group, 28 = experimental group). The mean scores of CompThink and Academic Achievement were analysed using a One-way MANOVA. Post-course testing revealed that learning achievement and CompThink were higher than students studying using traditional methods.
Keywords: Sample (material); Innovative Teaching Methods